2022
DOI: 10.1177/18479804221079419
|View full text |Cite
|
Sign up to set email alerts
|

The role of CNT in surface defect passivation and UV emission intensification of ZnO nanoparticles

Abstract: We report on the controlled enhancement of the UV emission from ZnO nanoparticles synthesized via hydrothermal sol-gel routes. Various characterization techniques were used in this study to determine the crystal structure, defect formation, morphology and size of the ZnO nanoparticles. Firstly, the crystallinity of the ZnO nanoparticles was assessed by X-ray diffraction. The role of the precursor quantities on their morphology and bandgap states was investigated via transmission electron microscopy and photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…Sample ZnO-Et aq (figure 3(d)) shows needle-like and hexagonally shaped nanoparticles. In a previous study, the effect of varying the NaOH molar ratio on the morphology of ZnO nanoparticles with an aqueous ethanol solvent was investigated [8]. The authors demonstrated that reaction kinetics leading to the growth of ZnO nanoparticles are accelerated by increasing quantities of OH − ions in the solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample ZnO-Et aq (figure 3(d)) shows needle-like and hexagonally shaped nanoparticles. In a previous study, the effect of varying the NaOH molar ratio on the morphology of ZnO nanoparticles with an aqueous ethanol solvent was investigated [8]. The authors demonstrated that reaction kinetics leading to the growth of ZnO nanoparticles are accelerated by increasing quantities of OH − ions in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the DLE is attributed to the combination of several point defects, such as V O , V Zn , O i, Zn i , and their complexes [45,46]. Whereas, the NBE emission originates from the recombination of excitons due to band-to-band transitions [8]. Moreover, the ratio of NBE-to-DLE is indicative of the crystalline quality of the sample.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have demonstrated that the ZnO-nanoparticle synthesis route has an enormous impact on its photocatalytic activity [ 7 , 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Synthesis routes tailor the morphology, size and specific surface of the nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…These various structures achieved by the nanostructures of ZnO make these materials unique, with a diverse set of characteristics and prospective uses in a variety of nanotechnology disciplines. Several methods for the synthesis of ZnO nanostructures have been reported, such as microemulsion synthesis [48,49], sol-gel techniques [50][51][52], mechanochemical processing [53,54], spray pyrolysis and drying [55,56], thermal decomposition of organic precursor [57,58], RF plasma synthesis [59,60], supercritical water processing [61,62], self-assembling [63], hydrothermal processing [64][65][66], vapor transport process [67,68], microwave assisted synthesis [69,70], direct precipitation, and homogeneous precipitation [71,72].…”
Section: Introductionmentioning
confidence: 99%